Influence of a scalar-isovector δ-meson field on the quark phase structure in neutron stars - Alaverdyan, Grigor Bakhshi (Research in astronomy and astrophysics, 2010)
The deconfinement phase transition from hadronic matter to quark matter in the interior of compact stars is investigated. The hadronic phase is described in the framework of relativistic mean-field theory, where the scalar-isovector 6-meson effec- tive field is also taken into account. The MIT bag model for describing a quark phase is used. The changes of the parameters of phase transition caused by the presence of a δ-meson field are explored. Finally, alterations in the integral and structural parameters of hybrid stars due to both a deconfinement phase transition and inclusion of a δ-meson field are discussed.